MITIGATING EFFECTS OF COMBINED ADMINISTRATION OF TURMERIC (CURCUMA LONGA) AND CUCUMBER (CUCUMIS SATIVUS) JUICE ON LEAD ACETATE INDUCED TESTICULAR DYSFUNCTION IN WISTAR RATS - Amadi N. G; Kolawole T. A; Saronee F; Amadi J. E; Olumeni V; Nwachukwu P. C; Jaja S. I; Dapper D. V (Western European Studies, 2025)
The present study investigated the mitigating effects of combined administration of Turmeric (Curcuma longa) and Cucumber (Cucumis sativus) juice on Lead induced testicular dysfunction in Wistar Rats. Twenty-five (25) male rats were randomly distributed into 5 groups (n=5). Testicular toxicity was induced by administering a daily oral dose of 2.25mg/kg bw of Lead acetate in all rat groups except group 1, and the rats were later grouped as follows: Group 1 (control); Group 2: (Lead (Pb) only); Group 3: Lead with 1ml Turmeric juice (Pb + TUM); Group 4: Lead with 1 ml Cucumber juice (Pb + CUC); Group 5: Lead with 1ml Turmeric juice and 1ml Cucumber juice (Pb + TUM + CUC) respectively. All interventions were orally administered with the aid of an oral cannula for 28days. On day 29, the rats were anesthetized with diethyl ether and caudal epididymides were separated and segmented for sperm analysis (Sperm count, viable sperm, non-viable sperm and Motility), also blood samples were collected by direct cardiac puncture for the determination of serum male reproductive hormones (Testosterone, Follicle Stimulating Hormone and Luteinizing Hormone) using ELISA kits. Results of sperm analysis revealed significant decrease (p < 0.05) in sperm count, viable sperm cells and sperm motility among Group 2 (Pb Only) rats while significant increase (p < 0.05) was observed in the number of non- viable sperm cells when compared to Group 1 (Control) rats. Significant (p < 0.05) improvements were observed amongst groups 3 (Pb + TUR) and 4 Pb + CUC) rats administered single daily dose of Turmeric and Cucumber juice individually when compared to Group 2 (Pb Only) rats, with Cucumber (Pb + CUC) juice showing a better outcome compared to Turmeric
Keywords: Turmeric; Cucumber; Toxicity; Reproductive hormones